Assessment of different genotyping markers and algorithms for distinguishing Plasmodium falciparum recrudescence from reinfection in Uganda - Alex Mwesigwa; Monica Golumbeanu; Sam Jones; Sara L. Cantoreggi; Benson Musinguzi; Joaniter I. Nankabirwa; Everd Maniple Bikaitwoha; Joan N Kalyango; Charles Karamagi; Mateusz Plucinski; Samuel L. Nsobya; Christian Nsanzabana; et al. (Scientific Reports)
Abstract Antimalarial therapeutic efficacy studies are vital for monitoring drug efficacy in malaria-endemic regions. The WHO recommends genotyping polymorphic markers including msp-1, msp-2, and glurp for distinguishing recrudescences from reinfections. Recently, WHO proposed replacing glurp with microsatellites (Poly-α, PfPK2, TA1). However, suitable combinations with msp-1 and msp-2, as well as the performance of different algorithms for classifying recrudescence, have not been systematically assessed. This study investigated various microsatellites alongside msp-1 and msp-2 for molecular correction and compared different genotyping algorithms across three sites in Uganda. Microsatellites 313, Poly-α, and 383 exhibited the highest diversity, while PfPK2 and Poly-α revealed elevated multiplicity of infection (MOI) across all sites. The 3/3 match-counting algorithm classified significantly fewer recrudescences than both the ≥ 2/3 and Bayesian algorithms at probability cutoffs of ≥ 0.7 and ≥ 0.8 (P < 0.05). The msp-1/msp-2/2490 combination identified more recrudescences using the ≥ 2/3 and 3/3 algorithms in the artemether-lumefantrine (AL) treatment arm, while msp-1/msp-2/glurp combination classified more cases of recrudescence using the ≥ 2/3 in the dihydroartemisinin-piperaquine (DP) arm. Microsatellites PfPK2 and Poly-α, potentially sensitive to detecting minority clones, are promising replacements for glurp. Discrepancies in recrudescence classification between match-counting and Bayesian algorithms highlight the need for standardized PCR correction practices.